PEMETAAN PEMASARAN PRODUK OLAHAN PANGAN LOKAL DI KABUPATEN SERANG - Emma Aswariny; Meutia Meutia; Aliudin Aliudin (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2020)
This research was conduct in Serang district, with three subdistrict namely Waringinkurung for emping, Pontang for bontot and Bojonegara for engkak cake. The purpose of this research is to describe mapping market of local food in Serang district. The snowball sampling was conducted including of 55 samples. The result show the average production of emping is 700,77 kg/week. The average production of bontot is 200,28 kg/week and the average production of engkak cake is 442,17 pan/week. Mapping market areas of emping and engkak cake is to markets outside area. Mapping market areas of bontot is to markets inside and outside area. The average selling price of emping in the manufacturer is Rp. 30.8884,62/kg, in collecting merchant is Rp. 32.250/kg, in wholesaler is Rp. 36.750/kg, and in retailers is Rp. 42.000,-/kg. The average selling price of bontot in the manufacturer is Rp. 24.000/kg, and in retailers is Rp. 26.000/kg. The average selling price of engkak cake in the manufacturer is Rp. 28.583,33/pan, and in retailers is Rp. 29.500/pan. The traffic mapping of emping was on foot, motorbike, private car, public transport car, and pick-up car. The traffic mapping of bontot and engkak cake was on foot and motorbike.